Cortical glutamate and GABA are related to compulsive behaviour in individuals with obsessive compulsive disorder and healthy controls - Biria, Marjan; Banca, Paula; Healy, Máiréad P.; Keser, Engin; Sawiak, Stephen J.; Rodgers, Christopher T.; Rua, Catarina; de Souza, Ana Maria Frota Lisbôa Pereira; Marzuki, Aleya A.; Sule, Akeem; Ersche, Karen; Robbins, Trevor W. (Nature Communications, 2023)
There has been little analysis of neurochemical correlates of compulsive behaviour to illuminate its underlying neural mechanisms. We use 7-Tesla proton magnetic resonance spectroscopy (1H-MRS) to assess the balance of excitatory and inhibitory neurotransmission by measuring glutamate and GABA levels in anterior cingulate cortex (ACC) and supplementary motor area (SMA) of healthy volunteers and participants with Obsessive-Compulsive Disorder (OCD). Within the SMA, trait and clinical measures of compulsive behaviour are related to glutamate levels, whereas a behavioural index of habitual control correlates with the glutamate:GABA ratio. Participants with OCD also show the latter relationship in the ACC while exhibiting elevated glutamate and lower GABA levels in that region. This study highlights SMA mechanisms of habitual control relevant to compulsive behaviour, common to the healthy sub-clinical and OCD populations. The results also demonstrate additional involvement of anterior cingulate in the balance between goal-directed and habitual responding in OCD.